2002
DOI: 10.1016/s0002-9440(10)64211-3
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomyxoma Peritonei Is a Disease of MUC2-Expressing Goblet Cells

Abstract: Pseudomyxoma peritonei, a syndrome first described by Karl F. Rokitansky in 1842, is an enigmatic, often fatal intra-abdominal disease characterized by dissecting gelatinous ascites and multifocal peritoneal epithelial implants secreting copious globules of extracellular mucin. Although past interest in the syndrome has focused on the questions of the site of origin (appendix versus ovary), mechanisms of peritoneal spread (multicentricity, redistribution phenomenon, or metastasis), and the degree of malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 39 publications
3
108
0
7
Order By: Relevance
“…Our recent molecular studies with pseudomyxoma peritonei and derived primary cell cultures have indicated that MUC2 expression is epigenetically regulated and susceptible to pharmacological regulation (42). This suggests that MUC2 may also be the primary molecular target for pseudomyxoma peritonei as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent molecular studies with pseudomyxoma peritonei and derived primary cell cultures have indicated that MUC2 expression is epigenetically regulated and susceptible to pharmacological regulation (42). This suggests that MUC2 may also be the primary molecular target for pseudomyxoma peritonei as well.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the results of previous reports. In 2002, O'Connell et al [8] demonstrated that MUC2 served as a reliable molecular marker of pseudomyxoma peritonei. In 2008, Semino-Mora et al [10] reported that the expression of MUC2 was drastically higher in peritoneal-free mucin and in mucinous neoplastic epithelia of pseudomyxoma peritonei compared with non-neoplastic appendiceal epithelia; additionally, these authors found that multiple enteric bacteria were present in pseudomyxoma peritonei and that bacterial density and MUC2 expression were higher in peritoneal-free mucin of pseudomyxoma peritonei compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…The rest lie somewhere in between and are classed as hybrids, which means the mucinous adenocarcinoma presents a hybrid pattern of distribution that shows features of the pattern seen with adenocarcinoma combined with the pattern seen with pseudomyxoma peritonei [5]. Right now, pseudomyxoma peritonei should be regarded as a disease of MUC2-expressing goblet cells [6]. Since 10 years ago, the standard treatment of pseudomyxoma peritonei was to remove as much of the tumor and mucus as possible in order to restore breathing and bowel functions.…”
Section: Discussionmentioning
confidence: 99%